The return of happiness: Resilience in times of pandemic - Michael Ahlheim; In Woo Kim; Duy Thanh Vuong (Universität Hohenheim, Fakultät Wirtschafts- und Sozialwissenschaften, 2022)
Many papers have been written about people's loss of life satisfaction during the first wave of the COVID-19 pandemic in 2020, but not much has been said about their resilience after the first shock had passed. Were people able to return, at least in part, to their original level of life satisfaction? This amounts to the question to which degree people had shown psychological resilience during the first wave of the COVID-19 crisis. In this context, it is also of interest which internal and external factors supported a person's tendency to prove resilient during the crisis. Based on an online survey conducted in August / September 2020 in Germany we try to answer these questions. We find that after a loss of average life satisfaction during the first three months after the outbreak of the pandemic in Germany many people's life satisfaction increased again. Roughly 60% of the respondents proved resilient in the sense that eight months after the outbreak of the pandemic they had regained the same or an even higher level of life satisfaction as compared to the situation before the COVID-19 crisis. Our results show that besides socioeconomic characteristics like age and income and certain character traits, people's personal experience during the crisis and their approval or disapproval of government policy during the crisis had an important influence on their chance to prove resilient. Therefore, a consistent and competent crisis communication building up trust in government's crisis management capacity is essential for people's resilience in a crisis.
urn:nbn:de:bsz:100-opus-20174
Keywords: I10; I12; I18; 330; Resilience; resistance; COVID-19; life satisfaction